Development of interactive learning media based on Lectora Inspire on the basics of building construction and soil measurement techniques - Petrus Desniatman Zega; Envilwan Berkat Harefa; Aprianus Telaumbanua; Arisman Telaumbanua (Edumaspul: Jurnal Pendidikan, 2024)
This research was based on a preliminary study at SMK Negeri 1 Mandrehe Barat, it was found that students were passive and monotonous in learning process activities and had not used interactive learning media which means the learning process was not optimal. The solution to this problem is to use interactive learning media based on Lectora Inspire in the learning process. The purpose of this research is to develop valid, practical and effective interactive learning media based on Lectora Inspire.This type of research is Research and Development (R&D) development research using the ADDIE model (Analize, Design, Developtment, Implementation, Evaluation). The instruments used in this study were validation questionnaires for feasibility tests, student and teacher response questionnaires for practicality tests, and essay question tests for testing the effectiveness of learning outcomes.The types of data used in this study are qualitative data and quantitative data. Qualitative data in the form of comments, and suggestions given by validators to the learning media developed. While quantitative data is in the form of questionnaire results from validators, student and teacher response questionnaires and learning outcome tests. Based on the results of the study, the interactive learning media based on Lectora Inspire developed has been tested and declared valid both in terms of material validity 95%, language validity 94%, and design validity 92. Furthermore, interactive learning media is also very practical to use by students based on the percentage of individual tests of 93%, field trials of 94%, and teacher responses of 93% practicality of 95.47% and the percentage of practicality results from teachers of 93.81%. Interactive learning media is also effective in increasing students' learning ability with an average score of 89% and is in the high category. So it can be concluded that the interactive learning media developed has met the expectations or research objectives.